Patients overview of pulp disease and periapical abnormalities at UPTD Puskesmas Baturiti II, Tabanan Bali: Gambaran pasien penyakit pulpa dan kelainan periapikal di UPTD Puskesmas Baturiti II, Tabanan Bali - Wibhu, I Dewa Gede Ananta; Pratama, I Wayan Agus Wirya (Makassar Dental Journal, 2024)
Pulp disease and periapical abnormalities are diseases that need to be treated to prevent infection or tooth loss, including at UPTD Puskesmas Baturiti II Tabanan Bali, Indonesia. The study was conducted in December 2023-February 2024 to determine the number of patient visits with pulp disease and periapical abnormalities. The study was conducted observationally with cross-sectional method. The results of this study showed that the number of patient visits with pulp disease and periapical abnormalities was 89 out of a total of 270 patients. It was concluded that the number of patient visits for pulp disease and periapical abnormali-ties was 89 out of a total of 270 patients. With this, more in-depth education about oral health is needed to minimise pulp dis-ease and periapical abnormalities.